Cytotoxic effect of helichrysetin on cancer cell lines and its mechanisms / Ho Yen Fong - Ho , Yen Fong (2017)
Helichrysetin is a naturally-occurring compound from the group of chalcones that is found in the Chinese ginger, seeds of some Alpinia sp. and flowers of Helichrysum sp.. Previous studies have shown that helichrysetin exhibits several biological activities such as antiplatelet aggregation, antioxidant, and anti-cancer activity. This compound has been found to be effective in the growth inhibition of human breast, liver and cervical cancer cell lines but no study on the molecular mechanisms has been performed. Hence, this research aims to study the growth inhibitory effect of helichrysetin on four selected cancer cell lines and it shows the highest activity on A549 and Ca Ski cell lines. The effect of helichrysetin on A549 cell line has been selected for further molecular investigation. In this study helichrysetin was found to inhibit A549 cells through the induction of apoptosis by triggering mitochondrial-mediated apoptotic pathway. Apoptotic cellular and nuclear morphological features were observed in the A549 cells after exposure to helichrysetin. Treatment with helichrysetin also resulted in the changes in the structure of cell plasma membrane, disruption in the mitochondrial membrane potential, cell cycle arrest and damage of DNA mainly internucleosomal DNA fragmentation in A549 cells. Proteomic study was performed to further understand the signaling cascades in the cells. The proteomic study has revealed the ability of helichrysetin to initiate cell death in A549 cells potentially by stimulating oxidative stress proven by the stimulation of oxidative stress markers HMOX1 and NRF2. Presence of oxidative stress in cells will result in DNA damage. In response to DNA damage, DNA damage response and cell cycle arrest are commonly triggered to allow for DNA repair. Results from this study showed that helichrysetin causes the suppression of proteins related to DNA damage repair such as p-ATM, BRCA1, and FANCD2 and Rb1 hence contributing to the impairment of DNA damage response in A549 cells. The inability of the cells to perform DNA repair will trigger the induction of apoptosis in the cells. Findings from this study have therefore proven the potential of helichrysetin as anti-cancer agent for the treatment of human lung cancer. The discovery of its mechanism of action on human lung cancer cells provides a better understanding and important information for the development of helichrysetin for future targeted-cancer therapy.